ANALYSIS OF REGULATIONS FOR DETERMINING THE LIMITED PROTECTION STATUS OF TERUBUK FISH (TENUALOSA MACRURA) PERMEN-KP NO. 210 OF 2023 REFERRING TO NO. 58/PERMEN-KP/2020 CONCERNING CAPTURE FISHERIES BUSINESSES - Thamrin, Thamrin; Harahap, Irawan; Oktapani, Silm (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
This research aims to determine the form of analysis, as well as determine the obstacles and constraints in implementing the Decree of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia Number: PERMEN-KP No. 210 of 2023 if guided by PERMEN-KP No. 58 of 2020 concerning capture fisheries businesses. In scientific research using a qualitative approach with an interpretative normative paradigm, the available theories used for research are constructed as an imperfect building, and this research is descriptive. In implementing the Decree of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia Number: PERMEN-KP No. 210 of 2023 concerning Limited Protection of Terubuk Fish (Tenualosa macrura) has not been implemented in the socialization, sea patrol and monitoring activities carried out by the Government, Indonesian National Army, Police and community monitoring groups. If PERMEN-KP No. 210 of 2023 is guided by PERMEN-KP No. 58 of 2020 concerning capture fisheries businesses, there will be discrepancies between the rules made and the rules applied in the field. The effectiveness of the implementation of the Decree of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia on the availability of fish resources legally and seen from fishermen's catches has increased and is quite effective, but it is not yet significant because sanctions for violations have not been realized and the obstacles and obstacles to the implementation of the Decree when referring to PERMEN-KP No. 58 of 2020 should not be needed. Fishermen who have small boats (< 5 gross tonnage) are allowed to catch terubuk (Tenualosa macrura) in conservation areas following PERMEN – KP No. 58 of 2020.